Critérios de classificaç\~ao para ocupaç\~ao informal: Consequências para a caracterizaç\~ao do setor informal e para a análise de bem-estar no Brasil - Carlos Henrique Corseuil; Mauricio Cortez Reis; Alessandra Scalioni Brito (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– In this paper we aim to analyze how sensible is the informal worker profile to distinct classification procedures, as well as to analyze the sensibility of the link between informality and welfare to the same procedures. A disaggregated analysis by employers and employees is one contribution of the paper, which also innovates using information on being included in an official tax payer administrative file (CNPJ) to one of the classification procedures employed to the employers. Two out of three procedures share very similar results in terms of informal worker profile and the link between informality and welfare. These are the procedure based on social security contribution, and the one based on CNPJ for employers and based on legal labor contracts for employees.
Keywords: R17; 330; informal sector